2000
DOI: 10.1080/15216540051081092
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxynonenal in the Pathomechanisms of Oxidative Stress

Abstract: Here we review the current knowledge on the biochemistry and molecular pathology of oxidative stress with specific regard to a major aldehydic end-product stemming from peroxidation of biomembranes, that is 4-hydroxynonenal (HNE). This multifunctional molecule, which derives from the most represented class of polyunsaturated fatty acids in the membranes, is potentially able to undergo a number of reactions with proteins, phospholipids, and nucleic acids. Despite an active metabolism in most of the cell types, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(163 citation statements)
references
References 25 publications
3
160
0
Order By: Relevance
“…Evidences from previous researches (Poli and Schaur 2000;Nakashima et al 2003) also indicated that the 4HNE is a key mediator of oxidative stress-induced cell death. 4HNE modulates several mechanisms inducing apoptosis such as, increasing the ROS production and altering mitochondrial respiratory and signal transductions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Evidences from previous researches (Poli and Schaur 2000;Nakashima et al 2003) also indicated that the 4HNE is a key mediator of oxidative stress-induced cell death. 4HNE modulates several mechanisms inducing apoptosis such as, increasing the ROS production and altering mitochondrial respiratory and signal transductions.…”
Section: Discussionmentioning
confidence: 85%
“…Effect of ALDH2 on 4HNE-Induced Increase in Intracellular Reactive Oxygen Species Level 4-Hydroxynonenal has been suggested to be a key mediator of oxidative stress-induced cell death and to induce mitochondrial oxidative stress (Poli and Schaur 2000;Raza and John 2006). In order to examine whether the inhibitory effect of ALDH2 on the toxicity of 4HNE is mediated by decreasing ROS level, neurons were treated with 10 lM 4HNE for 24 h, and the levels of ROS were measured using DCF fluorescence.…”
Section: Effect Of Aldh2 On the Loss Of Mitochondrial Transmembrane Pmentioning
confidence: 99%
“…Of primary concern is the ability to covalently modify cellular macromolecules. 4-HNE protein modifications have been implicated in the etiology of many disease states including mitochondrial dysfunction, atherosclerosis, Alzheimer's disease, diabetes, and alcoholic liver disease (Hartley et al, 1997;Poli and Schaur, 2000;Roede and Jones, 2010;Sampey et al, 2003). 4-HNE and 4-ONE also have the ability to modify nucleic acids and low levels of DNA adducts are abundant in both untreated rodent and human genomes (Sampey et al, 2003).…”
Section: -Hydroxynonenal and 4-oxononenalmentioning
confidence: 99%
“…An increasing number of reports provide evidence of a causative involvement of this biogenic aldehyde in the pathogenesis of a great number of inflammatory and degenerative processes, including atherosclerosis, Alzheimer's and Parkinson's diseases, liver fibrosis, glomerusclerosis, chronic obstructive bronco-pulmonary diseases and, last but not the least, atherosclerosis (see for a review [4]). With special regard to HNE potential involvement in the pathogenesis of atherosclerosis, this has been corroborated by consistent detection of the aldehyde in both oxLDL [3] and fibrotic plaque in humans [5].…”
Section: Chemistry and Biochemistry Of 4-hydroxynonenal (Hne)mentioning
confidence: 99%